The dopamine D1-D2 receptor heteromer in striatal medium spiny neurons: evidence for a third distinct neuronal pathway in basal ganglia - Melissa L. Perreault; Melissa L. Perreault; Ahmed eHasbi; Ahmed eHasbi; Brian F. O'Dowd; Brian F. O'Dowd; Susan R. George; Susan R. George (Frontiers Media S.A., 2011)
Dopaminergic signaling within the basal ganglia has classically been thought to occur within two distinct neuronal pathways; the direct striatonigral pathway which contains the dopamine D1 receptor and the neuropeptides dynorphin and substance P, and the indirect striatopallidal pathway which expresses the dopamine D2 receptor and enkephalin. A number of studies have also shown, however, that D1 and D2 receptors can co-exist within the same medium spiny neuron and emerging evidence indicates that these D1/D2-coexpressing neurons, which also express dynorphin and enkephalin, may comprise a third neuronal pathway, with representation in both the striatonigral and striatopallidal projections of the basal ganglia. Furthermore, within these coexpressing neurons it has been shown that the dopamine D1 and D2 receptor can form a novel and pharmacologically distinct receptor complex, the dopamine D1-D2 receptor heteromer, with unique signaling properties. This is indicative of a functionally unique role for these neurons in brain. The aim of this review is to discuss the evidence in support of a novel third pathway coexpressing the D1 and D2 receptor, to discuss the potential relevance of this pathway to basal ganglia signaling, and to address its potential value, and that of the dopamine D1-D2 receptor heteromer, in the search for new therapeutic strategies for disorders involving dopamine neurotransmission.